CHANGES IN THE ORAL MUCOSA AFTER ORTHODONTIC CONSTRUCTIONS - Asrorovna, Kholboyeva Nasiba; Qizi, Usanova Sarvinoz Ilkhom; Bakhodirovna, Sharipova Bonu (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: The aim of this study is to address the challenges associated with prosthetics, particularly complete removable dentures, which require specific conditions for fixation in the oral cavity. It also aims to explore the design considerations and post-treatment care to improve patient adaptation and the longevity of the prosthetic devices. Methods: The study focuses on the evaluation of various factors considered by orthopedic dentists when designing removable dentures. These factors include the condition of the temporomandibular joint (TMJ), the elasticity of mucous membranes, the presence of scars or cords, the degree of bone tissue atrophy, and the shape of the palate. After the prosthesis is delivered, patients are instructed on its use, as well as on specific speech exercises to aid in adaptation. Results: The findings highlight the importance of assessing the patient's oral condition before prosthetic design. Proper care and adaptation exercises post-prosthetic fitting significantly enhance the patient’s ability to adjust to the dentures, thus improving both comfort and effectiveness. Novelty: This study provides insights into the complexities of designing complete removable dentures and emphasizes the critical role of personalized care and speech training to facilitate faster adaptation and extend the lifespan of dentures.